Fonologi bahasa Bali di Desa Peliatan, Kecamatan Ubud, Kabupaten Gianyar : laporan penelitian - Sri, Anak Agung Putri (Universitas Udayana, 1992)
Phonology of Balinese language, spoken in Peliatan Village, Kecamatan Ubud, Kabupaten Gianyar, Bali Province; research report.